Strategies for Sustainable Development - Exploring the similarities and differences between the European Union and the Visegrad Four - Kozma Dorottya Edina; Козма Д. Е. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2019)
Abstract. The sustainable development like everyday concept and interpretation is a widely researched topic nowadays. In my study within the European Union, I examine the countries of the Visegrád Four in terms of sustainability. The Visegrád countries (also known as V4) have gone through great changes during the last two decades in terms of economic, social and environmental perspectives equally. The most important goal of my study is to determine what similarities and differences can be found in the surveyed EU member states or if we want to define in another way in sustainable development framework strategies and indicator systems of the Visegrad Four. I apply a comparative analysis for illustration that suits best the intended purpose.

A fenntartható fejlődés mint mindennapi fogalom és értelmezés, az elmúlt időszakban széles körben kutatott témává vált. Tanulmányomban az Európai Unión belül a Visegrádi négyek országait vizsgálom a fenntarthatóság szempontjából. A visegrádi országok (más néven V4) gazdasági, társadalmi és környezeti szempontból egyaránt nagy változásokon mentek keresztül az elmúlt két évtizedben. Legfontosabb célom annak meghatározása, hogy milyen hasonlóságok és különbségek találhatók a vizsgált EU-tagországok között. Más megfogalmazásban a visegrádi négyek fenntartható fejlődési keretrendszereit és indikátorrendszereit vizsgálom. Összehasonlító elemzést alkalmazok, ugyanis ez a módszer képes a legjobban bemutatni a kitűzött célt.
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2019_tom-vi_vi-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008405
Keywords: sustainable development; the Visegrad Four; comparative analysis